Clinical spectrum of non-syndromic microphthalmos, anophthalmos and coloboma in the paediatric population: a multicentric study from North India. Issue 7 (22nd August 2020) - Tibrewal, Shailja; Subhedar, Ketaki; Sen, Pradnya; Mohan, Amit; Singh, Shivanand; Shah, Chintan; Nischal, Ken K; Ganesh, Suma
Abstract : Aims: To describe the clinical features, visual acuity and causes of ocular morbidity in children (0–18 years) with microphthalmos, anophthalmos, and coloboma (MAC) from North India. Methods: A retrospective study conducted between October 2017 and September 2018 in three tertiary eye institutes, part of the Bodhya Eye Consortium with consensus led common pro formas. Children with complete clinical data and without syndromic/systemic involvement were included. The clinical phenotype was divided into isolated ocular coloboma (CB), coloboma with microcornea (CBMC), colobomatous microphthalmos (CBMO), non-colobomatous microphthalmos (MO) and anophthalmos (AO). Results: A total of 532 children with MAC were examined. Seventeen records were excluded due to incomplete data (0.2%). 515 children (845 eyes) were included: 54.4% males and 45.6% females. MAC was unilateral in 36% and bilateral in 64%. CB, CBMC, CBMO, MO and AO were seen in 26.4%, 31%, 22%, 8% and 12.5% of eyes, respectively. Nystagmus was found in 40%, strabismus in 23%, cataract in 18.7% and retinal detachment in 15%. Best-corrected visual acuity (BCVA) of <3/60 was seen in 62.4% eyes. Blindness (BCVA <3/60 in better eye) was seen in 42.8% of bilateral patients. Those with microcornea or microphthalmos with coloboma had worse BCVA (p<0.001). There were regional differences in the type of MAC phenotype presenting to the three institutes. Conclusion: The MAC group of disorders cause significant ocular morbidity. The presence of microcornea or microphthalmos with coloboma predicts worse BCVA. The variation of the MAC phenotype with the district of origin of the patient raises questions of aetiology and is subject to further studies.